Răspuns:
Explicație pas cu pas:
a)
a = 2√3 - √48 + 5√2 - √18
a = 2√3 - 4√3 + 5√2 - 3√2
a = - 2√3 + 2√2
b = 3√2 - √50 - 4√3 + √108
b = 3√2 - 5√2 - 4√3 + 6√3
b = - 2√2 + 2√3
c = 6√2 - √32 - 5√3 + √27
c = 6√2 - 4√2 - 5√3 + 3√3
c = 2√2 - 2√3
a + b + c = - 2√3 + 2√2 + ( - 2√2 + 2√3 ) + 2√2 - 2√3
a + b + c = - 2√3 + 2√2 - 2√2 + 2√3 + 2√2 - 2√3
a + b + c = 2√2 - 2√3
a - b + c = - 2√3 + 2√2 - ( - 2√2 + 2√3 ) + 2√2 - 2√3
a - b + c = - 2√3 + 2√2 + 2√2 - 2√3 + 2√2 - 2√3
a - b + c = - 4√3 + 4√2 + 2√2 - 2√3
a - b + c = - 6√3 + 6√2.